Pengembangan Media Pembelajaran Interaktif untuk Meningkatkan Budaya Toleransi di SDN Pondok Bambu 15 Pagi - Pratama, Nauval Satria; Laily, Annida Nur Alfi; Madya, Dika Putra; A'yun, Virza Qurrota (TSAQOFAH, 2025)
Building a culture of tolerance among children is made more difficult by the growing ethnic and cultural diversity at State Elementary School 15 Pondok Bambu Pagi, which is the subject of this study. Different student backgrounds can lead to divergent opinions and possible confrontations; therefore, it's important to really try to teach them the value of tolerance. Researching and developing interactive learning materials in the form of digital comics with the goal of promoting the comprehension and implementation of intercultural tolerance ideals in the classroom is the goal of this research. Research and development (R&D) is the methodology employed in this study, and questionnaires and interviews were utilized to gather data. Two Islamic religious education educators were interviewed in order to determine the requirements and expectations in the advancement of the media. Data on the quality assessment of the produced media, which was based on assessments by media and material specialists, was also gathered through questionnaires. It is intended that this digital comic medium would help the students of SDN Pondok Bambu 15 Pagi develop a more tolerant culture.